Counselor competency, self-efficacy, and inmates' readiness to change in drug abuse treatment and rehabilitation centers in Malaysia / Abd Halim Mohd Hussin - Abd Halim, Mohd Hussin (2010)
This study examined the relationship between counselor competency and selfefficacy, and the relationship between those two variables with inmates' stage of readiness to change in drug abuse rehabilitation centers in Malaysia. Two groups of respondents were involved in this study, namely, the practicing counselors who are anti-drugs officers in government-funded rehabilitation centers in Malaysia, and the inmates undergoing treatment at the re-entry stage. The respondents comprised the whole population of 263 counselors and 703 inmates. Two sets of self-administered questionnaires, namely, the Self-Rating Addiction Counseling Competency Scale (SRACCS) and Counselor Self-Efficacy Scale (CSES), were distributed to the counselors, while the Stage of Change Scale (SoCS) was distributed to the inmates. 12 different domains of rating scales were used in the SRACCS while 3 subscales were used in the CSES, with both having reliability estimates (Cronbach's Coefficient Alpha) of above .90. The instrument used to measure the readiness to change (SoCS) had a Cronbach alpha of .75. The findings of this study indicate that the competency levels of counselors in 12 domains were at moderate level, with a general mean of 2.49, whilst self-efficacy was at a moderately high level of 4.12 on a six-point scale. Inmates' readiness to change was also identified to be at a moderate level. There was a moderately strong positive correlation between counselor competency and self-efficacy, and between those two variables and the inmates' level of readiness to change. This study showed that all the counselors had a high level of responsibility related to their work but lacked knowledge and skills. There was a significant relationship between competency and type of training, academic qualification and work experience. Knowledge, skills and attitudes in two sub-scales of competency, Understanding Addiction and Treatment Knowledge, contributed significantly to selfefficacy. The results of analyses on inmates' readiness to change at the re-entry phase of rehabilitation showed that about 70% of them were still at the Contemplation stage, with a small percentage at the Action stage, and a small number still at the Precontemplation stage. These findings point to a need to closely review the effectiveness of the drug rehabilitation efforts. This study has revealed a need for a close and critical look at the training and development of professional helpers as well as treatment modalities. The findings have meaningful and important implications for the National Agency on Drug Abuse in particular and the country in general.